A Conceptual Model of Children's Active Play Imagery. Issue 3 (3rd July 2018) - Guerrero, Michelle; Munroe-Chandler, Krista
ABSTRACT: Imagery research with children has been primarily examined within a structured physical activity context. However, researchers have begun to investigate children's imagery use in their active play (i.e., unstructured leisure-time physical activity). The objective of the present article was to develop a conceptual model of active play imagery—the active play imagery model. This objective was accomplished by applying the components of the revised applied model of deliberate imagery use (RAMDIU; Cumming and Williams, 2013) to the context of active play. The proposed model comprises the same seven components included in the RAMDIU (i.e., where and when, who, why, what and how, meaning, imagery ability, and outcomes). However, in contrast to the RAMDIU, the active play imagery model acknowledges that individual characteristics can directly influence one's ability to image. The proposed model will provide a guiding framework for future research and applications of active play imagery.